2005
DOI: 10.1007/bf02430392
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in polymer Ni-MH battery

Abstract: Abstract. The alkaline solid polymer electrolyte system with the conductivity of (8.5 -0.2) x 104 Scm -~ composes of polyvinyl alcohol (PVA) and potassium hydroxide (KOH) have been used in fabrication of Mg2Ni/Ni(OH)2 nickel metal hydride cell. The self-dehydriding of the cell during storage was presented by open circuit voltage study. Cell degradation after charge-discharge cycling is characterized by means of X-ray diffraction and scanning electron microscopic analyses. The failure of the cell can be ascribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, the next discharge capacities, nearly stable at about 331 mAh•g -1 , were higher than that of the traditional KOH electrolyte Ni-MH batteries and other relevant documents obviously. [9,21] These results revealed that the Mg 2 NiH 4 alloys, inside of the electrode, were prevented more corrosion by using the PVA/SiO 2 AMPEs than the conventional KOH aqueous electrolyte and the corrosion resistance of the whole alloys improved.…”
Section: Electrochemical Stability Measurementmentioning
confidence: 89%
“…However, the next discharge capacities, nearly stable at about 331 mAh•g -1 , were higher than that of the traditional KOH electrolyte Ni-MH batteries and other relevant documents obviously. [9,21] These results revealed that the Mg 2 NiH 4 alloys, inside of the electrode, were prevented more corrosion by using the PVA/SiO 2 AMPEs than the conventional KOH aqueous electrolyte and the corrosion resistance of the whole alloys improved.…”
Section: Electrochemical Stability Measurementmentioning
confidence: 89%
“…The excess OH − ions attacked the rest of the Mg active material, converting it to the Mg(OH) 2 passive material. Mohamad et al [8,14] demonstrated that the XRD and SEM of the Mg 2 Ni-based anode, fully changed to Mg(OH) 2 upon cycling in 6 M KOH aqueous electrolyte.…”
Section: Methodsmentioning
confidence: 98%
“…The solid electrolytes that have been used such as Sb 2 O 5 .nH 2 O [1,2] and tetramethylammonium hydroxide penthydrate [3]. Meanwhile, for the alkaline solid polymer electrolytes (ASPE), those that have been reported were polyacrylamide gel [4], poly(ethylene oxide) [5], copolymer of epichlorohydrin and ethylene oxide P(ECH-co-EO) [6], polyvinyl alcohol (PVA) [7][8][9][10], poly(acrylic acid) (PAA) [11] and PVA-PEO-glass fiber mat [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is no fire hazard associated with Mg-Ni aqueous solution rechargeable batteries. Unfortunately, the high electrochemical capacity of Mg (or Mg alloy) attenuates very quickly after a dozen charging-discharging cycles due to Mg (or Mg alloys) suffering severe corrosion in an aqueous alkaline solution (4). Using a non-aqueous solid polymer electrolyte (SPE) membrane to replace the caustic alkaline solution will prevent the Mg from corroding and greatly increase the cycle life.…”
Section: Introductionmentioning
confidence: 99%